Program Psikologi Terpadu dan Strategi Komunikasi Untuk Mendukung Gerakan Desa Sehat Bebas Stunting di Desa Nanjung - Widyastuti, Linda; Anissaniwaty, Myrna; Rambe, Ira Hasianna; Panjaitan, Yoko Jimmy; Ardiva, Elsya; Samrotussolihat, Loviani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Stunting is a severe health issue in Indonesia, impacting the physical and cognitive development of children. Objective: This program aims to support stunting prevention and control through integrated psychological and communication strategies in Nanjung Village, Bandung Regency. Method: To educate the community on stunting prevention using appropriate psychological and communication programs and empower families to support optimal child growth and development. Result: Activities included counseling, training, and family assistance at risk of stunting through the integration of psychology and communication sciences. The program successfully increased community awareness of the importance of nutrition, psychological health, and communication within families. The risk of stunting in children decreased. Conclusion: Integrated psychological and communication approaches significantly contribute to stunting control efforts.